1978
DOI: 10.1159/000232094
|View full text |Cite
|
Sign up to set email alerts
|

Early Rheumatoid-Like Lesions in Rabbits Injected with Foreign Serum: Relationship to Localization of Immune Complexes in the Lining Tissues of Joints and Cellular Content of Synovial Fluid

Abstract: Immune complex localization in joint tissues and white cell effusion into the joint space as well as synovial lesions are shown to occur in rabbits injected intravenously with bovine serum. Synovial lesions of one knee were found to be associated with immune complexes in joint tissues of the contralateral knee (because of the experimental design very few rabbits had both immunofluorescence and histology performed on the same joint). There was also a week correlation between moderate and gross synovial lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Rabbits injected intravenously with bov ine serum according to certain regimens de velop synovial lesions which, in their histopathology, resemble those found in rheuma toid disease [Poole and Coombs, 1977;Poole et al" 1978). In a further report [Old ham and Coombs, 1980] a small group of 3 rabbits was injected repeatedly with bovine milk instead of with bovine serum and only 1 out of these New Zealand White (NZW) rabbits developed mild joint lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits injected intravenously with bov ine serum according to certain regimens de velop synovial lesions which, in their histopathology, resemble those found in rheuma toid disease [Poole and Coombs, 1977;Poole et al" 1978). In a further report [Old ham and Coombs, 1980] a small group of 3 rabbits was injected repeatedly with bovine milk instead of with bovine serum and only 1 out of these New Zealand White (NZW) rabbits developed mild joint lesions.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that rabbits injected intravenously with bovine serum develop rheumatoid-like joint lesions [Poole and Coombs, 1977], More recently we have shown these rabbits to have immune com plexes deposited in joint tissues and to have white cell effusions in the joint space [Poole et al, 1978], In these experiments only a percentage of those animals injected, devel oped lesions, and these lesions were of a moderate nature only. It was felt that if this deposition of complexes in the joint tissues could be enhanced, then the percentage of animals developing lesions and the intensity of the lesions might be increased.…”
Section: Introductionmentioning
confidence: 87%
“…Histological and joint fluid studies were as de scribed previously [Poole and Coombs, 1977;Poole et al 1978],…”
Section: Histology and Joint Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological and joint fluid studies were as de scribed previously [Poole and Coombs, 1977;Poole et al, 1978]. Joint lesions were scored on a 0 to + + + + scale, depending on the joint tissue changes (see footnote to table I).…”
Section: Histology and Joint Fluidsmentioning
confidence: 99%